Factors influencing students' behavioral intention to use an online learning portal - Tang, Hasnah King Yee; Wong, Su Luan; Mohd Ayub, Ahmad Fauzi; Ibrahim, Norliza; Moses, Priscilla (Faculty of Educational Studies, Universiti Putra Malaysia, 2009)
The widespread introduction of Information Technology and the Internet is reshaping the landscape of the learning environment, namely online education. It is important to note that, to achieve a successful online education, it is important to understand the determinants of online learning among students. Therefore, this research study aims to explore the factors that can influence students' behavioral intention to use an online learning portal. In view of that, a comprehensive search of the literature was carried out. The literature review reveals that gender, students' attitude, perceived ease of use, perceived usefulness, motivation and social interaction influence an individual's intention to use an online learning portal. Indeed, online learning has changed the learning culture forever.